Avaliação temporal e espacial dos atributos químicos e microbiológicos do solo em sistemas de produção de morango de Turuçu/RS - Islabão, Gláucia Oliveira (2009)
Strawberry crop is an important option for small properties, being of great relevance for people fixation at countryside and generation and maintenance of rural jobs. Studies related to soil attributes monitoring, which can be used as soil quality indicators, are important to evaluate the sustainability of agricultural practices and to point to sound environment management, aiming to its conservation. This work intended to analyze the spatial and temporal variability of the chemical and microbiological soil attributes during the strawberry crop cycle in fourteen rural properties affiliated to the Association of Strawberry Producers of Turuçu-RS, to identify and evaluate the potential impacts of irrigation water on these attributes and to propose actions to minimize these impacts if needed. In this way, deformed soil samples were collected in four different periods at depth 0-0.20 m, to determine their chemical attributes (organic matter, active and potential acidity, CEC and at pH 7.0, base saturation and aluminum saturation), microbiological (carbon and nitrogen of microbial biomass, basal respiration and metabolic quotient) and about fertility (total nitrogen, phosphorus, potassium, copper and zinc). In order to evaluate the mean values of all attributes along the time in each property was applied the LSD mean comparison test with significance to 5%. The spatial and temporal variability of all attributes were evaluataded by means of box plots. Results indicated that between the soil chemical indicators, the mean values of potential acidity presented the major significant variation along the time, while the mean values of aluminum saturation presented the minor variation. Between the soil microbiological indicators, the mean basal respiration presented the major significant variation along the time, while the mean values of nitrogen of microbial biomass presented the minor variation. Between soil fertility indicators the mean values of copper presented the major significant variation along the time, while the mean values of zinc presented the minor variation. With regard to the spatial and temporal variability of the chemical indicators it was found that organic matter presented the greatest amplitude and the aluminum saturation the lowest. Regarding to the spatial and temporal variability of the microbiological indicators it was found that carbon of microbial biomass presented the greatest amplitude while the metabolic quotient presented the lowest. Regarding to the spatial and temporal variability of the soil fertility indicators it was found that copper presented the greatest amplitude while zinc presented the lowest. The concentrations of phosphorus, potassium, copper and zinc presented high levels in all strawberry crops. The organic matter levels were classified as low in most strawberry crops. It was not possible to identify the impact of irrigation water over the chemical and soil fertility indicators, meanwhile, there was a possible impact over the microbiological indicators, specially over the carbon and nitrogen of microbial biomass and metabolic quotient.